Prophylactic Use of Metronidazole during Major Gynaecological Operation to Prevent Wound Infection: A Randomized Control Trial - Khatun, Mahmuda; Banu, Dewan Sahida; Sultana, Rifat; Millat, Md Asadul; Mondal, Dipika Rani; Mahmud, Shahabuddin; Ahmad, Ashfaq (Bangladesh Journal of Infectious Diseases, 2018)
Background: Prophylactic medication of major gynaecological operations is very important for the reduction of bad surgical outcomes. Objective: This randomized control trial was conducted to determine whether the metronidazole prophylaxis in conventional therapy was effective in controlling postoperative wound infection in major gynaecological infection. Methodology: The study was carried out at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during .the period from August 2002 to January 2003. One hundred and fifty consecutively admitted patients for gynecological operation were randomly assigned to receive either metronidazole and ampicillin/amoxicillin (group A) or only ampicillin/amoxicillin (group B) just after operation and continued for 7 days. After operation, daily follow-up with observation of the wound was done till their discharge. All the outcome data were collected, compiled and statistically analyzed using SPSS programme with the consultation of the statistician. Result: A total number of one hundred and forty patients were referred of which 70 patients from group A and 70 from group B. Wound infection was observed in 4(5.7%) patients of group A and 6(8.6%) patients of group B. There was no significant difference (P>0.747) in only considering abdominal wound infection and also in including vaginal wound infections (P>0.747). Conclusion: The study findings show that metronidazole prophylaxis in conventional therapy is an extremely effective agent in controlling anaerobic wound infection after gynaecological surgery. Bangladesh Journal of Infectious Diseases 2017;4(1):10-14